Development of the double-contour protection concept in socio-cyberphysical systems - Pohasii, Serhii; Milevskyi, Stanislav; Tomashevsky, Bohdan; Voropay, Natalya (Національний технічний університет "Харківський політехнічний інститут", 2022)
The rapid development of mobile Internet technologies LTE (Long-Term Evolution) not only predetermined the further development of cyber-physical systems, which are based on the synthesis of technologies of classical computer systems and LTE technologies, as well as integration with Internet-of-Things technologies. As a result, the emergence of sociocyberphysical systems predetermines further development based on this integration. The creation of mesh- and sensor networks also allows the development of smart technologies and systems based on their conglomeration. The development and creation of a quantum computer, on the one hand, will make it possible to make a technical breakthrough in computing resources, use artificial intelligence, and on the other hand, it can lead to "chaos" in ensuring the security of modern technologies and systems. So, based on the algorithms of Shor and Grover quantum cryptography, symmetric cryptosystems based on traditional cryptography algorithms, as well as asymmetric cryptosystems, including systems based on elliptic curve cryptography, can be broken. The paper proposes to use a new approach to building security systems based on the concept of internal and external security contours. At the same time, security contours of continuous business processes are considered. This approach provides an objective assessment of the current state of security of the socio-cyber system as a whole.

Бурхливий розвиток мобільних інтернет-технологій LTE (Long-Term Evolution) не тільки зумовив подальший розвиток кіберфізичних систем, що ґрунтуються на синтезі технологій класичних комп'ютерних систем та технологій та LTE, а також комплексуванні з технологіями інтернет-речей. Внаслідок чого поява соціокіберфізичних систем визначає подальший розвиток на основі даного комплексування. Створення mesh-, сенсорних мереж дозволяє також розвивати смарттехнології, і системи, засновані на їх конгломерації. Розвиток та створення квантового комп'ютера з одного боку дозволить зробити технічний прорив у обчислювальних ресурсах, використовувати штучний інтелект, а з іншого боку може призвести до "хаосу" у забезпеченні безпеки сучасних технологій та систем. Так на підставі алгоритмів квантової криптографії Шора та Гровера можуть бути зламані симетричні криптосистеми на основі алгоритмів традиційної криптографії, а також несиметричні криптосистеми, включаючи системи на основі криптографії на еліптичних кривих. У роботі пропонується використовувати новий підхід до побудови систем безпеки на основі Концепції внутрішнього та зовнішнього контурів безпеки. У цьому розглядаються контури безпеки безперервних бізнеспроцесів. Такий підхід забезпечує об'єктивну оцінку поточного стану безпеки соціокіберсистеми загалом.
Розробка концепції двоконтурного захисту соціокіберфізичних систем
Keywords: double-contour Security concept; post-quantum period; quantum computer; synergy; hybridity of cyberattacks; двоконтурна Концепція безпеки; постквантовий період; квантовий комп'ютер; синергізм; гібридність кібератак